Friction and wear of polymer composites - Friedrich, Klaus, 1945- (Composite materials series, 1986)
Providing a useful summary of current knowledge on the friction and wear properties of composite materials, this book fills the gap between publications on fundamental principles of tribology and those on the friction and wear behavior of metals and polymers. Detailed coverage is given of: the fundamental aspects of tribology in general and polymer composites in particular; the effects of the microstructure of composites on friction and wear behavior under different external loading conditions; and the problem of the control of friction and wear behavior in practical situations. Although emphasis is on polymer composites associated with bearing-type applications, part of the book is also devoted to the friction and wear of metal-based composites and rubber compounds. The data are represented in the form of 277 figures, diagrams and photographs, and 68 tables. The author index covers more than 670 references, and the subject index more than 1,000 keywords. The book will be of particular interest to: those involved in research on some aspects of polymer composites tribology (material scientists, physical chemists, mechanical engineers); those wishing to learn more methods for solving practical friction or wear problems (designers, engineers and technologists in industries, dealing with selection, reprocessing and application of polymer engineering materials); and teachers and students at universities.